Barrett’s Esofagus - Syifa Mustika; Bayu Eka Nugraha (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Gastroesophageal reflux disease (GERD) is a condition commonly managed in the primary care setting. Patients with GERD may develop reflux esophagitis as the esophagus repeatedly is exposed to acidic gastric contents. Over time, untreated reflux esophagitis may lead to chronic complications such as esophageal stricture or the development of Barrett’s esophagus (BE). BE may progress to oesophageal adenocarcinoma. There is currently a rising incidence of BE. The pathogenesis of BE is not well-understood although genetic and environmental factors play significant roles. BE is characterized by the replacement of distal esophageal stratified squamous epithelium by columnar epithelium. It is rare in children and the risk factors may include mental retardation, cerebral palsy, esophageal atresia, etc. As patients with BE can be entirely asymptomatic, it is difficult to screen this population group. BE is present in 10%–20% of patients with GERD and has also been detected in patients who deny classic GERD symptoms and are undergoing endoscopy for other indications.